Continuity and change in older adults' perceptions of out-of-home mobility over ten years: a qualitative-quantitative approach - Mollenkopf, Heidrun; Hieber, Annette; Wahl, Hans-Werner (Ageing & society, 2011)
This research report starts from the assumption that a solely geriatric and transport-related view of out-of-home mobility needs to be extended to incorporate other aspects of perceived and experienced mobility. In particular, our goal is to understand better the stability and change in people's perceptions of out-of-home mobility over ten years. We concentrate on: (a) the subjective meaning of mobility over time, including perceived changes in mobility and perceived reasons for change; (b) trends in satisfaction with various mobility domains; and (c) a case-oriented exploration of inter-individual variation over time. A qualitative-quantitative data-analytic approach was applied to data collected from 82 participants on three occasions over ten years in 1995, 2000 and 2005. The mean age of the sample in 2005 was 75.2 years. The results indicate overall stability in the meaning attached to mobility between 1995 and 2005, while the perceived changes point to major losses in the array of mobility experiences and decreasing satisfaction with mobility opportunities, out-of-home leisure activities and travelling, but in contrast satisfaction with public transport increased. Case studies exemplified the reasons for the pronounced variation in satisfaction with mobility dynamics over time. In conclusion, the findings confirm that out-of-home mobility remains of utmost importance when people move from late midlife into old age.
Gesehen am 01.09.2022